Achieving the Saying in the Interpretation of the Almighty's Saying (The Night of Fasting is Permitted for you...) {187: Al-Baqarah} - Atallah Saleh, Nizar (Dirasat: Human and Social Sciences, 2022)
This study deals with the interpretative issues in the interpretation of verse No. 187 of Surat Al-Baqarah, which deals with fasting and the intimate relationship between a man and his wife. The researcher relied on an analytical method, where he followed the views of the commentators on these issues and weighed them after looking at the evidence. The research reached a number of results. Among the most prominent of these results is that the statement of abrogation in this verse is due to the reasons for the revelation. It is true that there is no abrogation in this verse. In addition, the word “permissible for you” does not denote the permissibility after the prohibition, but rather it denotes absolute permissibility Moreover, the term “takhtanuun” has nothing to do with treason in its general sense. Rather, it is about the soul being deprived of some of its rights that Allah has placed in the human instinct.